2018
DOI: 10.1021/acs.biomac.8b01355
|View full text |Cite
|
Sign up to set email alerts
|

Surface Coassembly of Polymer Brushes and Polymer–Protein Bioconjugates: An Efficient Approach to the Purification of Bioconjugates under Mild Conditions

Abstract: Well-defined polymer–protein bioconjugates are widely used in therapeutics and biocatalysis. One of the challenges in the synthesis of bioconjugates is the efficient separation of the target conjugate molecules from reaction systems. In this research, surface coassembly of polymer brushes and polymer–protein bioconjugates is investigated, and it is demonstrated that the coassembly approach can be applied in the purification of polymer–protein bioconjugates. Bovine serum albumin-poly­(N-isopropylacrylamide) (BS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 43 publications
0
39
0
Order By: Relevance
“…We ando ther researchers have demonstrated that the conjugation of proteins to thermally responsivep olymers could change the phase-transition temperatures of the polymers significantly. [21][22][23][24] The shift in the phasetransition temperature of PNIPAM in PPL nanogelsi sa ttributed to the incorporation of PPL molecules to the network structures and an increase in the hydrophilicity of the polymer. After coating with BSA, the endotherm of PNIPAM shifts to the high-temperature regime.…”
Section: Resultsmentioning
confidence: 99%
“…We ando ther researchers have demonstrated that the conjugation of proteins to thermally responsivep olymers could change the phase-transition temperatures of the polymers significantly. [21][22][23][24] The shift in the phasetransition temperature of PNIPAM in PPL nanogelsi sa ttributed to the incorporation of PPL molecules to the network structures and an increase in the hydrophilicity of the polymer. After coating with BSA, the endotherm of PNIPAM shifts to the high-temperature regime.…”
Section: Resultsmentioning
confidence: 99%
“…Surface co‐assembly method can be applied in the fabrication of biosurface. In a recent publication, Hou and coworkers reported the synthesis of biosurface and protein purification by co‐assembly of polymer‐protein bioconjugates and polymer brushes on silica particles . Bovine serum albumin‐poly(N‐isopropylacrylamide) (BSA‐PNIPAM) bioconjugate was used as a model bioconjugate.…”
Section: Surface Nanostructures Fabricated By Surface Co‐assembliesmentioning
confidence: 99%
“…[10] Herein, we demonstrate that coassembly of homopolymer brushes and block copolymer chains can be used to control the surface composition and wetting behavior of the solid surfaces.S urface micelles on silica particles are prepared by the coassembly approach, and the cores are crosslinked by the photodimerization of anthracene (Scheme 1). [10] Herein, we demonstrate that coassembly of homopolymer brushes and block copolymer chains can be used to control the surface composition and wetting behavior of the solid surfaces.S urface micelles on silica particles are prepared by the coassembly approach, and the cores are crosslinked by the photodimerization of anthracene (Scheme 1).…”
mentioning
confidence: 99%
“…As determined by size exclusion chromatography (SEC), the apparent molecular weights (Mns) and molecular weight dispersities (PDIs) of the two polymers are 13.2 K, 1.24 and 24.5 K, 1.18 ( Figure S2). [10,11] Silica particles with an average size of 180 nm were synthesized by the Stçber method ( Figure S3), [12] and the particles were decorated with pyridyl disulfide groups (SiO 2ss-Py) by two-step surface reactions. Based on 1 HNMR analysis ( Figure S1b), the repeating unit number of DMAEMA in the block copolymer was determined to be 60.…”
mentioning
confidence: 99%
See 1 more Smart Citation